(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetic neuropathy is one of the most common microvascular complications of diabetes mellitus and is a major cause of morbidity among affected individuals. Chronic hyperglycemia contributes to nerve damage through multiple metabolic and vascular mechanisms. Glycated hemoglobin (HbA1c) serves as a reliable indicator of long-term glycemic control and may be associated with the severity of diabetic neuropathy. Aim: To evaluate the association between HbA1c levels and the severity of diabetic neuropathy among patients with type 2 diabetes mellitus. Materials and Methods: A hospital-based observational cross-sectional study was conducted in the Department of Medicine in collaboration with the Department of Obstetrics and Gynaecology at Nirmala Multispeciality Hospital, Rewari, Haryana, from January 2025 to August 2025. A total of 50 patients with type 2 diabetes mellitus and diabetic neuropathy were enrolled. Demographic and clinical data were collected using a structured proforma. HbA1c levels were measured using standardized laboratory methods. Neuropathy severity was assessed using the Michigan Neuropathy Screening Instrument (MNSI) and categorized as mild, moderate, or severe. Statistical analysis was performed using SPSS version 26.0. Pearson’s correlation and one-way ANOVA were applied to assess the association between HbA1c levels and neuropathy severity. Results: The mean age of the study participants was 56.8 ± 9.4 years, with males accounting for 58% of the study population. The mean duration of diabetes was 8.7 ± 4.1 years, and the overall mean HbA1c level was 8.9 ± 1.7%. Mild, moderate, and severe neuropathy were observed in 32%, 42%, and 26% of patients, respectively. Mean HbA1c levels increased significantly with neuropathy severity, measuring 7.3 ± 0.9% in mild neuropathy, 8.8 ± 1.2% in moderate neuropathy, and 10.2 ± 1.1% in severe neuropathy (p < 0.001). A strong positive correlation was observed between HbA1c levels and neuropathy severity scores (r = 0.71, p < 0.001). Patients with severe neuropathy also had a significantly longer duration of diabetes compared with those having mild or moderate neuropathy (p < 0.001). Conclusion: Higher HbA1c levels are significantly associated with increased severity of diabetic neuropathy among patients with type 2 diabetes mellitus. Poor glycemic control and longer duration of diabetes contribute substantially to neuropathy progression. Regular monitoring of HbA1c and maintenance of optimal glycemic control may help reduce the burden and severity of diabetic neuropathy.